2005
DOI: 10.1111/j.1875-595x.2005.tb00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine abuse: orofacial manifestations and implications for dental treatment

Abstract: Millions of individuals in Europe and the United States use cocaine regularly. Use of cocaine may have several orofacial effects such as perforation of nasal septum and palate, gingival lesions and erosion of tooth surfaces. Recent use of cocaine may also increase medical risks during dental treatment, especially when local anaesthetics with epinephrine or epinephrine-impregnated retraction cords are used. Therefore, it is recommended to postpone dental treatment at least 6 to 24 hours after the use of cocaine. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
0
39
0
1
Order By: Relevance
“…34 The majority of the patients with cocaine-induced palatal necrosis are female (72%), despite the fact that more men than women use cocaine. 13 There fore, it has been suggested that women are more susceptible to this complication of cocaine usage. 14 Patients with a palatal perforation suffer from serious speech impairment.…”
Section: Palatal Perforationmentioning
confidence: 99%
“…34 The majority of the patients with cocaine-induced palatal necrosis are female (72%), despite the fact that more men than women use cocaine. 13 There fore, it has been suggested that women are more susceptible to this complication of cocaine usage. 14 Patients with a palatal perforation suffer from serious speech impairment.…”
Section: Palatal Perforationmentioning
confidence: 99%
“…In addition, the use of meth, cocaine, and heroin has been associated with an increased occurrence of dental disease (Richards & Brofeldt 2000;Rosenstein 1975;Blanksma & Brand 2005;Kapila & Kashani 1997).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Cocaine is often applied to gingiva or to the alveolar mucosa to test the drug's purity and can be used to relieve the pain of cluster headaches. [2][3][4] Other recreational drugs such as methylenedioxymethamphetamine (MDMA) 52 and amphetamine in association with cocaine 53 have been reported as causes of mucosal ulceration and periodontitis following oral application.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include local application of medications (eg aspirin), recreational drugs (cocaine), some materials commonly used by dentists, and non-pharmaceutical substances. [2][3][4] We report a case of chemical oral ulceration as a result of an intentional suicidal acute exposure to sulphuric acid and we present a review of the literature concerning chemical oral ulceration.…”
Section: Introductionmentioning
confidence: 99%